Analisis Efektivitas Kunyit Hitam (Curcuma caesia Roxb.) Dalam Penurunan Kadar Mikroalbumin dan Serum Kreatinin Pada Tikus Diabetes Nefropati - Zakiyyah Qurrotu Aini; Tri Wijayanti; Aldita Cahyani Puspitasari (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: Diabetes mellitus (DM) is a chronic degenerative disease whose prevalence continues to increase. Treatment of DM with pharmacological therapy is often expensive and causes side effects. This study explores the effectiveness of black turmeric (Curcuma caesia Roxb.) in reducing complications of diabetic nephropathy by reducing microalbumin and creatinine. The purpose of this study was to analyze the effectiveness of black turmeric rhizome extract (Curcuma caesia Roxb.) in reducing serum creatinine and microalbumin levels in diabetic nephropathy model rats. Methods: This study used an in vivo method with rats induced with diabetes using STZ-NA and testing was carried out for 45 days. Serum creatinine and microalbumin were measured using a spectrophotometer and immunoturbidimetry. Results: This study showed that black turmeric extract at a dose of 400 mg/kg BW had an effectiveness equivalent to the positive control in reducing serum creatinine and microalbumin levels. The decrease in serum creatinine reached 20.10%, while the decrease in microalbumin reached 11.88%. The antioxidant and polyphenol content in black turmeric plays a role in reducing oxidative stress and inhibiting apoptosis in ? cells, which has an impact on reducing blood sugar levels and improving kidney function. Conclusion: Black turmeric extract (Curcuma caesia Roxb.) is effective in reducing serum creatinine and microalbumin levels in diabetic nephropathy model rats, with an optimal dose of 400 mg/kg BW. This study supports the potential of black turmeric as a natural therapeutic agent for diabetic nephropathy complications.